Subdivision of Mycobacterium tuberculosis for epidemiological purposes: a seven year study of the "Classical' and 'Asian' types of the human tubercle bacillus in South-East England. - Grange, J. M. (Cambridge University Press, 1985)
Human strains of Mycobacterium tuberculosis were divided into the 'Classical' and 'Asian' types according to their sensitivity to thiophen-2-carboxylic acid hydrazide. The isolation of these two types in South-East England was studied during a seven-year period (1977-1983). The 'Asian' type was more prevalent among ethnic Asian patients than among ethnic Europeans. Among Europeans there was a decline in the isolation rate of 'Classical' strains and a small but significant increase in 'Asian' strains during the study period, so that the proportion of the latter type in this group is increasing. The type of bacillus was unrelated to the site of isolation except that the incidence of lymphadenitis due to the 'Asian' type among European females was significantly higher than expected. In general, European patients tended to be older than Asian patients, and the differences in age distribution according to site of isolation and type of bacillus in each ethnic group were small. A notable exception occurred with European females infected with the 'Asian' type, whose age distribution was similar to the Asians. In view of the differences in behaviour of the two types of human tubercle bacilli in this country there is a need to continue a bacteriological surveillance and also to determine whether the nature of the host-pathogen interaction varies according to the type of bacillus.